A Workshop on Writing in National Journals Accredited by SINTA for Master of Science Education Students - Aris Doyan; Susilawati Susilawati; Saprizal Hadisaputra; Syamsul Hakim; Muhammad Taufik (Unram Journal of Community Service, 2022)
This scientific article writing workshop is a service activity aimed at students of the Master of Science Education Postgraduate at the University of Mataram. This activity was attended by 20 students. The purpose of this service is to help students to be more productive in compiling scientific articles from various data that have been obtained through literature studies, research results, or the preparation of papers. This workshop was conducted by the method of discussion and assistance in writing articles by a team of service lecturers. The result of the implementation of this workshop is that each student can compile good articles and choose an accredited journal SINTA as a journal to publish articles